Multiple regulation mechanisms of bacterial quorum sensing - Kumberger, Peter; Kuttler, Christina; Czuppon, Peter; Hense, Burkhard A. (Biomath, 2016)
Many bacteria have developed a possibility to recognise aspects of their environment or to communicate with each other by chemical signals. The so-called Quorum sensing (QS) is a special case of this kind of communication. Such an extracellular signalling via small diffusible compounds (called autoinducers) is known for many bacterial species, including pathogenic and beneficial bacteria. Using this mechanism allows them to regulate their behaviour, e.g. virulence. We will focus on the typical QS system of Gram negative bacteria of the so-called lux type, based on a gene regulatory system with a positive feedback loop. There is increasing evidence that autoinducer systems themselves are controlled by various factors, often reflecting the cells’ nutrient or stress state. We model and analyse three possible interaction patterns. Typical aspects are e.g. the range of bistability, the activation threshold and the long term behaviour. Additionally, we aim towards understanding the differences with respect to the biological outcomes and estimating potential ecological or evolutionary consequences, respectively.
Gesehen am 04.06.2020